2001
DOI: 10.1177/000331970105200503
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of QT Dispersion in Patients With and Without Coronary Artery Disease

Abstract: QT dispersion defined as interlead QT variability in a 12-lead electrocardiogram was proposed by Day and associates as a simple method to evaluate the repolarization heterogenicity of the ventricular myocardium. The frequency of onset of myocardial infarction and sudden death has been reported to have a circadian variation, with a peak incidence in the early morning hours. The authors investigated whether there is diurnal variation of QT interval and QT interval dispersion in healthy subjects and in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Using all 12 leads available Yetkin et al 19 and Batur et al 20 observed a significantly higher QTc dispersion in the morning and daytime compared to nighttime, whereas Lee et al 10 agreed with our observation that QT dispersion had a higher value at night compared to daytime. Malik et al 23 did not find any significant difference between day and night in a 12‐lead Holter recording.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Using all 12 leads available Yetkin et al 19 and Batur et al 20 observed a significantly higher QTc dispersion in the morning and daytime compared to nighttime, whereas Lee et al 10 agreed with our observation that QT dispersion had a higher value at night compared to daytime. Malik et al 23 did not find any significant difference between day and night in a 12‐lead Holter recording.…”
Section: Discussionsupporting
confidence: 90%
“…Circadian variation of QT dispersion in healthy subjects has been suggested by Ishida et al, 8 Molnar et al, 9 Lee et al, 10 Yetkin et al, 19 Batur et al, 20 Bilan et al, 21 and Bonnemeier et al, 22 but the results are contradictory and the studies have different setups in respect to number of leads used, measurement frequency, and whether heart rate correction of QT dispersion is used or not.…”
Section: Discussionmentioning
confidence: 98%
“…However, no previous study has addressed the possibility that the QT C and QT dispersion might change from daytime to night-time. A finding observed in patients with ischemic heart disease [39,40]. This might be caused by 24-h variation of autonomic tone, circulatory status, and respiratory and oxygen demand.…”
Section: Discussionmentioning
confidence: 96%
“…The circadian variation in QT dispersion has been investigated in healthy subjects, 9,10 patients with coronary artery disease, 11,12 and congestive heart failure 13,14 with conflicting observations. These studies vary in selection of leads and timing of measurements and therefore the results are difficult to compare.…”
mentioning
confidence: 99%